Three level supply chain model with variable demand rate under partial trade credit policy. (2015) - Singh, Narayan; Vaish, Bindu; Singh, S.R.
In this study, we generalise a partial trade credit policy in a three echelon supply chain system involving a single manufacturer, a single distributor and a single retailer. Here the manufacturer provides a delay period to the distributor and the distributer offers less trade credit period to the retailers, and the retailer also offers the partial trade credit to his customers. Demand and production rate are considered time dependent. This article develops an integrated inventory model to determine the minimum system cost, the optimal cycle time, optimal order quantity and optimal payment time. Suitably selected numerical examples highlight the obtained results. Sensitivity analysis of the optimal solution with respect to major parameters of the system has been carried out and the implications are discussed.